Plasma interleukin-22 concentration and disease activity in inflammatory bowel disease - Claudia Cabrera; Daniel Fernández-Llaneza; Marita Olsson; Charles Sopp; Tara Fehlmann; Elizabeth A. Duncan; Emon Khan; Junmei Cairns; Jessica Neisen; Ulf Gehrmann; Nick Powell (Scientific Reports)
Abstract The relationship between interleukin-22 and clinical characteristics of patients with inflammatory bowel disease is uncertain. We sought to determine whether plasma interleukin-22 concentrations are associated with disease activity in a large population of patients with inflammatory bowel disease. This was an observational study of patients with Crohn’s disease or ulcerative colitis in the Study of a Prospective Adult Research Cohort with IBD (SPARC IBD) from the IBD Plexus registry of the Crohn’s & Colitis Foundation in the United States. Interleukin-22 concentrations were measured using an R&D Systems human interleukin-22 enzyme-linked immunosorbent assay. Of 3993 patients included, 1604 with Crohn’s disease and 836 with ulcerative colitis had non-missing interleukin-22 baseline samples, of which 33% and 25%, respectively, were above the lower limit of quantification (7.8 pg/mL). Significantly more patients with moderate/severe disease activity had high interleukin-22 concentrations (above lower limit of quantification) versus those with remission/mild disease activity (Crohn’s disease: 44.7% vs. 30.0%, P < 0.00001; ulcerative colitis: 39.8% vs. 23.0%, P < 0.001). A multinomial logit model found approximately twice the odds of moderate/severe disease activity in those with high interleukin-22 versus low interleukin-22 (below lower limit of quantification). The strongest predictors of high interleukin-22 concentrations identified by a machine-learning algorithm were higher Short Crohn’s Disease Activity Index score in patients with Crohn’s disease and prescription of biologics in patients with ulcerative colitis. In summary, high interleukin-22 concentrations tended to be associated with higher disease activity in this large, real-world population of patients with inflammatory bowel disease.